5x-3=2x+26

Simple and best practice solution for 5x-3=2x+26 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x-3=2x+26 equation:


Simplifying
5x + -3 = 2x + 26

Reorder the terms:
-3 + 5x = 2x + 26

Reorder the terms:
-3 + 5x = 26 + 2x

Solving
-3 + 5x = 26 + 2x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-2x' to each side of the equation.
-3 + 5x + -2x = 26 + 2x + -2x

Combine like terms: 5x + -2x = 3x
-3 + 3x = 26 + 2x + -2x

Combine like terms: 2x + -2x = 0
-3 + 3x = 26 + 0
-3 + 3x = 26

Add '3' to each side of the equation.
-3 + 3 + 3x = 26 + 3

Combine like terms: -3 + 3 = 0
0 + 3x = 26 + 3
3x = 26 + 3

Combine like terms: 26 + 3 = 29
3x = 29

Divide each side by '3'.
x = 9.666666667

Simplifying
x = 9.666666667

See similar equations:

| 7w+3w=40 | | 7r^2+91r+280=0 | | 23=13+2a | | 200+2x=4x+400 | | 9b-36=0 | | -7x-14y=14 | | -2(5-3x)-6(2x-4)=x+1 | | -12+4t=0 | | 3(5x+39)=(X+26) | | -2x+17=x+8 | | 25=25+9r | | v=25(30) | | -2x+17=8+x | | -12r-48=12 | | -(5-3x)-6(2x-4)=x+1 | | 24x^4=36x^3-12x^2/12x^2 | | 19+3c=40 | | 7log(4x-1)=14 | | 5b-5.25b+3=3.75 | | -4c+5=9 | | -12x^2/12x^2 | | 3y+6=6-5x | | -6n-8=10 | | 7ln(4x-1)=14 | | 7+5d=42 | | (3x-40)+(2x+11)=180 | | tan(59)=.125/x | | 2(x+3)5=9 | | 11p=144 | | (-2x+2)=y | | 7k-45=4 | | 1-3x=8-4x |

Equations solver categories